Post-Thatcher fiscal strategies in the UK : an interpretation - Andrew Hughes Hallett (Center for Economic Studies and ifo Institute (CESifo), 2004)
Fiscal policy in Britain has changed radically since the Keynesianism of the 1960s and 1970s. After a passive period under monetarism of the 1980s, fiscal policy is said to have adopted a leadership role with long term objectives (low debt, the provision of public services/ investment, and social equity), together with an independent central bank. Monetary policy, operating with instrument independence, then takes care of short run stabilisation. I test this view – confronting it with evidence from the institutional arrangements put in place since 1997; with econometric evidence from the policy responses themselves; and with theoretical evidence on the incentive to choose such a regime in the first place. I conclude that this claim is broadly correct. It appears that the UK's improved performance is a consequence of the advantages of combining fiscal leadership with an (instrument) independent central bank. The key feature is the ability to trade target (not instrument) independence in monetary policy to secure greater coordination between fiscal and monetary strategies.
Keywords: E61; E52; F42; 330; Stackelberg leadership; policy complementarity; institutional coordination; Finanzpolitik; Geldpolitik; Zentralbankautonomie; Reaktionsfunktion; Schätzung; Grossbritannien